Point-of-Care Ultrasound to Assess Gastric Content. Issue 8 (August 2020) - Moake, Matthew M.; Jackson, Benjamin F.; Presley, Bradley C.
Abstract : Abstract: Gastric ultrasound (US) is a growing modality within the point-of-care ultrasound (POCUS) field. It provides the ability to directly measure an individual patient's gastric content and has potential use as both a clinical and a research tool. Here, we review the historical development of current gastric US models and their clinical application within the field of general anesthesia, describe the US findings and technique for using POCUS to assess gastric content, and discuss the current and potential applications of gastric POCUS within the emergency department. Abstract : Supplemental digital content is available in the text.